The Relationship between Diet and Suicide Risk and Resilience in Wildland Firefighters. (14th June 2022) - Bode, Katherine; Smith, Logan; Wells, Tony; Wollenberg, Gena; Joyce, Jllian
Abstract: Objectives: 1) To determine the nutrient intake and diet quality of wildland firefighters (WLFF); 2) to determine the relationship between diet quality and mental health indices (e.g., anxiety, depression, post-traumatic stress, suicidality) among WLFF. Methods: This cross-sectional study involved a convenience sample of 37 WLFF recruited via social media from across the US. Dietary intake was assessed via 24-hour recall entered into nutrient analysis software and scored using the Healthy Eating Index 2015 (HEI) for diet quality. Mental health was assessed using several indices for suicidality, anxiety, depression, hopelessness, and alcohol use. Nutrient intake and HEI scores were compared to current US adult intake patterns from the National Health and Nutrition Examination Survey (NHANES). Relationships between HEI scores and mental health indices were determined using Pearson correlation coefficients. Results: Mean (± standard deviation) age was 40.0 ± 11.7 years and 87.1% of participants were Caucasian with body mass index of 28.1 ± 4.5 kg/m 2 . Mean HEI score was 52.5 ± 14.8 out of 100, 10.6% lower than the US adult population. Added sugar, refined grains, and total protein all had scores between 81–100/100, indicating adequate intake. Total HEI, saturated fat, total vegetable, and sodium scores were between 51–80/100, indicating need for improvement. Seafood/plant protein, dairy, whole grains, and total fruit scores were between 0–50/100, indicating poor intake. Relationships between HEI scores and mental health indices were significant, moderate, and inverse (beneficial) for total HEI, dark greens and legumes, and fatty acid ratio scores with Alcohol Use Disorder Identification Test, Generalized Anxiety Disorder 7-item, and Patient Health Questionnaire. Conclusions: Diet quality for the diets of WLFF is lower than the US adult population, in significant need of improvement, and potentially impacting mental health status. Funding Sources: Not applicable.